Hubungan Antara IQ, EQ, dan AQ Dengan Prestasi Studi Pada Siswa SMU - Tjundjing, Sia (Faculty of Psychology, Universitas Surabaya, 2001)
The intelligence quotient (IQ) and lately the emotional quotient (EQ) have been much studied and discussed, involving the relation of these scores with academic achievements (AA). Stoltz's introduction of adversity quotient (AQ) leads this study to examine its relation with the AA, and meanwhile also revisit the relation of IQ and EQ with the AA. Subjects are second grade high school students sampled through a purposive clustered sampling. Data were collected from EQ tests with EQ-¡of Reuven Bar-On (1995) and AQ tests with ARP Quick Take TM of Stoltz (1997). The IQ score were obtained from the guidance & counseling department of the school based on a test by a psychology counselling bureau. Data were analysed with the SPSS programme for Windows. Results indicate the positive correlation between school report grades with the IQ of the students, but neither with the EQ nor the AQ of the students concerned. These results are discussed and further study design improvements are recommended. Masalah kuosien inteligensi (IQ) dan akhir-akhir ini kuosien emosional (EQ) telah banyak diteliti dan dibahas, demikian pula kaitannya dengan prestasi akademik. Diperkenalkannya kuosien keterpurukan/adversity quotient (AQ) oleh Stoltz (1997) mendorong penulis untuk mencari hubungannya dengan prestasi akademik. Subjek adalah siswa-siswa kelas dua sebuah SMU (N = 79) yang diperoleh dengan purposive clustered sampling. Data dari uji EQ dengan EQ-jÌM dari Reuven Bar-On (1996) dan uji AQ dengan ARP Quick Takedari Stoltz (1997). Skor IQ diperoleh dari bagian Bimbingan & Konseling berdasarkan uji oleh sebuah biro konsultasi psikologi. Analisis data dilakukan dengan menggunakan program SPSS 10.0 for Windows. Hasilnya menunjukkan korelasi positif antara nilai rapor dengan IQ siswa, namun tidak dengan EQ maupun AQ-nya. Hasil ini dibahas dan disarankan perbaikan desain untuk penelitian selanjutnya.